Analysis of disturb coupling faults coverage by the March AZ2 algorithm in memory BIST - Md Zin, Ahmad Ridhwan; Jidin, Aiman Zakwan; Razaidi, Hussin; Mispan, Mohd Syafiq (2024)
Memory BIST is a method implemented on chips to test memories by executing a sequence of test operations defined by the applied test algorithm. The March AZ2 test algorithm has been recently created to provide an excellent balance between the test fault coverage and test complexity to ensure fast and low-cost memory testing without compromising the test quality. Nonetheless, its ability to detect Disturb Coupling Faults (CFds) is not proven, as its creation purpose is focusing on other static faults’ detections. Therefore, this paper presents a comprehensive analysis of the March AZ2 algorithm’s coverage of CFds through a fault detection analyzer. It identifies the existence of sensitizer and detector test operations for each CFds fault primitive within the March AZ2 algorithm’s test sequence based on the described detection requirements. The analysis demonstrates that the March AZ2 algorithm provides 79.2% coverage of CFds by detecting 19 out of 24 fault primitives. By comparing it to other 14 N -complexity test algorithms like the March C+, it provides a higher overall CFds coverage than the latter.